Conserved Patterns in Backbone Torsional Changes Allow For Single Base Flipping from Duplex DNA with Minimal Distortion of the Double Helix - Banavali, Nilesh K. (2006)
Base flipping is a structural mechanism common to many DNA processing and repair enzymes. Changes in the local backbone torsions that occur during base flipping and the effect of environment on their behavior are of particular interest in understanding different base flipping mechanisms. In the present study, structures sampled during umbrella sampling molecular dynamics (MD) simulations of base flipping in aqueous and protein-bound environments, carried out with two different MD simulation strategies, are analyzed to find the most significant phosphodiester backbone distortions in the vicinity of the flipping base. Torsional sampling on the 5′ side of the flipping base during flipping through the major groove show similarities to the torsional sampling on the 3′ side during flipping through the minor groove and vice versa. In differing environments, this behavior varies only marginally. These compensating torsional changes in the DNA backbone on 5′ and 3′ sides of the flipping base limit overall distortion of the DNA double helix during single base flipping. Rotameric intermediate states observed during base flipping are identified and postulated to be metastable states implicated in both large-scale structural changes and functional effects of chemical modifications in DNA.